Penerapan Teknik Akrostik dalam Pembelajaran Menulis Puisi Pada Siswa Sekolah Dasar - Ratmiati - -; Sunarti - - (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Thisstudyaims toimprove poetry writing skills with acrostic techniques in elementary school students. This research is descriptive qualitative. This type of research is a class action research (Class Action Research). The research carried out consisted of two cycles, each cycle being carried out three times.TheThe research procedure includes planning, implementing the action, observing and reflecting. The subjects in this study were 34 grade V elementary school students.After carrying out the research in the first cycle 21 of 34 students got a score of 72.35 who got a